Futurelessness and Commitment to Institutional Rules Among People in Jail - Abderhalden, Frances P. (International journal of offender therapy and comparative criminology, 2024)
The current study builds on prior work examining the association between futurelessness and commitment institutional rules among correctional populations. Using cross-sectional data from a sample of 413 people incarcerated in United States jails from 2018 to 2019, this study employs Ordinary Least Squares regression to examine the association between futurelessness and commitment to institutional rules controlling for various importation and deprivation factors previously linked with institutional misconduct. Results provide support for the importance of futurelessness for commitment to institutional rules, suggesting that this finding is consistent across correctional environments. In addition, findings suggest that an index measure of futurelessness is a stronger construct for testing futurelessness than single-item measures used in prior studies. Consistent with prior literature on futurelessness, our findings suggest that among people incarcerated in jail futurelessness is linked to a weaker commitment to institutional rules.